Treaty of Ghent collection
Photograph of the former home of the Carthusians in Ghent where the treaty was signed; photograph of the house where the Americans commissioned to sign the treaty stayed; photocopies of certificates of election of the American commissioners to honorary memberships in Belgian societies; photocopies of portraits and sketches of the commissioners by P. van Huffel; and memorandum (1936 March 28) of J. Franklin Jameson describing the aforementioned items and citing their provenance. Commissioners include John Quincy Adams, James A. Bayard, Henry Clay, and Albert Gallatin with Christopher Hughes as secretary.
In part, positive and negative photocopies.
Collection material in English, with French and Italian.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John Quincy, -- 1767-1848 -- Portraits; Bayard, James A. -- 1767-1815 -- Portraits; Clay, Henry, -- 1777-1852 -- Portraits; Gallatin, Albert, -- 1761-1849 -- Portraits; Huffel, P. van; Hughes, Christopher, -- 1786-1849 -- Portraits; Jameson, J. Franklin -- 1859-1937.; Great Britain. -- 1814 December 24.; Artists -- Belgium; Carthusians -- Belgium -- Ghent; Dwellings -- Belgium -- Ghent; Associations, institutions, etc. -- Belgium